Soybean NADP-Malic Enzyme Functions in Malate and Citrate Metabolism and Contributes to Their Efflux under Al Stress - Zhou, Ying; Yang, Zhenming; Xu, Yuezi; Sun, Haoran; Sun, Zhitao; Lin, Bao; Sun, Wenjing; You, Jiangfeng (Frontiers in Plant Science, 2018)
Citrate efflux under Al stress has been identified as an Al-exclusion mechanism in soybean. Malate accumulation was suggested to balance Al-induced citrate synthesis and efflux in soybean roots. To test this hypothesis, characteristics of Al-induced accumulation and efflux of citrate and malate were compared between two soybean genotypes; GmME1 putatively encode a cytosolic NADP-malic enzyme was functionally analyzed to study its contribution to organic acid efflux. Similar amounts of citrate were released, and root elongation was equally inhibited before 8 h of Al treatment of Jiyu 70 and Jiyu 62 cultivars. Jiyu 70 began to secrete more citrate and exhibited higher Al resistance than did Jiyu 62 at 12 h. A sustained increase in internal malate and citrate concentrations was observed in Jiyu 70 at 24 h of Al treatment. However, Jiyu 62 decreased its malate concentration at 12 h and its citrate concentration at 24 h of Al treatment. Higher NADP-malic enzyme activities were observed in Jiyu 70 than in Jiyu 62 at 24 h of Al treatment. GmME1 clustered closely with cytosolic malic enzymes AtME2 and SgME1 and was constitutively expressed throughout whole soybean plant, with especially higher levels in the roots. Al treatment induced higher expression levels in Jiyu 70 than in Jiyu 62 at 24 h. Subcellular localization in Arabidopsis protoplasts showed that GmME1 localized to the cytoplast. Compared with wild-type hairy roots, over-expressing GmME1 in hairy roots (GmME1-OE) produced higher expression levels of GmME1 but did not change the expression patterns of either of the putative citrate transporter genes GmAACT1 and GmFRDL or the malate transporter gene GmALMT1, with or without Al treatment. GmME1-OE showed a higher internal concentration and external efflux of both citrate and malate at 4 hours of Al stress. Lighter hematoxylin staining and lower Al contents in root apices of GmME1-OE hairy roots indicated greater Al resistance. Comprehensive experimental results suggest that sustaining Al-induced citrate efflux depends on the malate pool in soybean root apices. GmME1 encodes a cytosolic malic enzyme that contributes to increased internal malate and citrate concentrations and their external efflux to confer higher Al resistance.